2016
DOI: 10.3892/etm.2016.3760
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of contrast-enhanced ultrasound compared with conventional ultrasound in acute pancreatitis: Diagnosis and complication monitoring

Abstract: Contrast-enhanced ultrasound (CEUS) has been used for diagnosing acute pancreatitis (AP), particularly severe acute pancreatitis (SAP). However, the diagnostic difference between CEUS and conventional ultrasonography (CUS) for AP and SAP has not been reported. The aim of the present study was to investigate the diagnostic accuracy of CUS and CEUS for AP. A total of 196 patients clinically diagnosed with AP were selected. All patients underwent CUS, CEUS and contrast-enhanced computed tomography (CECT) within 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
10
1
1
Order By: Relevance
“…Studies performed by Rademacher et al [4] and Lim et al [9] also presented an increase in the time of entrance and peak enhancement in dogs with pancreatitis. Results of CEUS technique were not effective in differentiation of altered tissues in most cases, however, it was possible to detect microvascularization, contrary to the study performed by Cai et al [24] which demonstrated that in cases of acute pancreatitis, this method allows successful identifi cation of changes in comparison to B mode ultrasonography, with an accuracy of 78.0% (103/132) and 47.7% (63/132), respectively. Vanderperren et al [25] also verifi ed a differentiation of exocrine and endocrine pancreatic tumors using CEUS: adenocarcinomas were presented hypovascular and insulinomas were hypervascular.…”
Section: Resultscontrasting
confidence: 56%
“…Studies performed by Rademacher et al [4] and Lim et al [9] also presented an increase in the time of entrance and peak enhancement in dogs with pancreatitis. Results of CEUS technique were not effective in differentiation of altered tissues in most cases, however, it was possible to detect microvascularization, contrary to the study performed by Cai et al [24] which demonstrated that in cases of acute pancreatitis, this method allows successful identifi cation of changes in comparison to B mode ultrasonography, with an accuracy of 78.0% (103/132) and 47.7% (63/132), respectively. Vanderperren et al [25] also verifi ed a differentiation of exocrine and endocrine pancreatic tumors using CEUS: adenocarcinomas were presented hypovascular and insulinomas were hypervascular.…”
Section: Resultscontrasting
confidence: 56%
“…Golea et al [74] concluded that contrast-enhanced ultrasound (CEUS) is usefulness in the quantification of the necrosis area in AP. Cai et al [76] conducted a study to evaluate the accuracy of conventional US and CEUS in patients with AP, concluding that CEUS is a reliable method for the diagnosis and prognosis of AP, and it may serve as a substitute for CECT. Skouras et al [77], by studying the characteristics of lung ultrasonography and its role in the diagnosis of respiratory dysfunction, proposed that this exam may be an adjuvant in the assessment of the severity of pancreatitis.…”
Section: Transabdominal Ultrasonographymentioning
confidence: 99%
“…Out of 27 clinical studies, seven fulfilled the inclusion criteria and were included in the meta-analysis [9,[16][17][18][19][20][21]. There was a total of 421 AP cases.…”
Section: Resultsmentioning
confidence: 99%